2020
DOI: 10.1093/toxres/tfaa078
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the cytotoxic, genotoxic and oxidative stress effects of the synthetic cannabinoid JWH-018 in human SH-SY5Y neuronal cells

Abstract: Background: JWH-018 was the first synthetic cannabinoid introduced as a legal high and the first of the new generation of novel psychoactive substances that flooded worldwide drug markets. JWH-018 was marketed as “spice,” “herbal incense,” or “herbal blend,” as a popular and legal (at the time) alternative to cannabis (marijuana). JWH-018 is a potent synthetic cannabinoid with considerable toxicity associated with its use. JWH-018 has qualitatively similar but quantitatively greater pharmacological effects tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…The treatment with fentanyl induces a high number of either annexin V-FITC and/or PI-stained cells, and increased levels of Bax and caspase 3 activity, supporting a double mechanism of cell death. It should be noted that the concentrations of drugs used in our in vitro study are higher than those found in urine or blood of drug abusers [85][86][87]; however, our data are consistent with several studies reporting in vitro cytotoxic effects (i.e., reduced viability at concentrations >1-2 mM) after exposure to several drugs of abuse, including cathinones, amphetamine-like stimulants, phenethylamines, and synthetic cannabinoids [41,[88][89][90][91][92]. It should also be considered that, due to their high lipophilicity, fentanyl and cathinone derivatives possess a high volume of distribution, reaching significantly greater concentrations in lipophilic tissues, such as the central nervous system [93], and consequently, their blood concentrations might not directly reflect their organ/tissue levels.…”
Section: Discussionsupporting
confidence: 89%
“…The treatment with fentanyl induces a high number of either annexin V-FITC and/or PI-stained cells, and increased levels of Bax and caspase 3 activity, supporting a double mechanism of cell death. It should be noted that the concentrations of drugs used in our in vitro study are higher than those found in urine or blood of drug abusers [85][86][87]; however, our data are consistent with several studies reporting in vitro cytotoxic effects (i.e., reduced viability at concentrations >1-2 mM) after exposure to several drugs of abuse, including cathinones, amphetamine-like stimulants, phenethylamines, and synthetic cannabinoids [41,[88][89][90][91][92]. It should also be considered that, due to their high lipophilicity, fentanyl and cathinone derivatives possess a high volume of distribution, reaching significantly greater concentrations in lipophilic tissues, such as the central nervous system [93], and consequently, their blood concentrations might not directly reflect their organ/tissue levels.…”
Section: Discussionsupporting
confidence: 89%
“…This is in contrast to the study conducted by Wojcieszak et al (2016) who demonstrated that CB2 receptor agonist JWH-133 produced a concentration-dependent decline of SH-SY5Y cell viability and reproduction rate, and in contrast to the study conducted by Fisher et al (2016) who showed that medication with cannabidiol (CBD) reduced the viability and invasiveness of NBL cells and stimulated apoptosis in vitro. In line with our study, Sezer et al (2021) indicated that JWH-018, a non selective cannabinoid agonist, did not cause a significant reduction, in SH-SY5Y cell viability, did not modify apoptotic/necrotic rate, and did not induce genotoxicity in SH-SY5Y cells with one day exposure; Cioni et al (2019) demonstrated that COR167 significantly decreased the proliferation of both anaplastic astrocytoma and glioblastoma in a dose-dependent manner; Sánchez et al (2001) indicated that JWH-133 decreased the growth of tumors derived from C6 cell line, but this effect was prevented by the selective CB2 antagonist SR144528. The level of reactive oxygen species is one of the factors that play an significant role in the development and metastasis of tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Despite their potential therapeutic use in a wide variety of pathologies and conditions, synthetic cannabinoids are associated with toxicity and several adverse effects [ 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 ]. Focusing on the synthetic cannabinoids that demonstrated medical potential, namely those belonging to the JWH, HU and AM series, the present section describes the toxicological effects observed.…”
Section: Toxicity Of Synthetic Cathinones and Synthetic Cannabinoidsmentioning
confidence: 99%
“…Moreover, the cellular mechanism underlying this effect was explored. Sezer and collaborators observed an increment in oxidative stress by increasing MDA levels, decreasing the activity of glutathione reductase (GR) and catalase, responsible for the detoxification of peroxide hydrogen (H 2 O 2 ), reducing glutathione levels (GSH), a known endogenous antioxidant that protect cells from oxidative reactions [ 269 ]. Based on these results and considering that studies indicate that JWH-133 has therapeutic potential, the authors call for caution in its possible use as this substance may accumulate in the CNS and lead to neuronal damage [ 266 ].…”
Section: Toxicity Of Synthetic Cathinones and Synthetic Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation